ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII MTSN 3 LIMA PULUH KOTA - Rani, Siti Maha; Imammuddin, M. (Universitas Tanjungpura, 2023)
This study aims to analyze the mathematical communication skills of class VIII students of MTsN 3 Fifty Kota which are still low. This type of research used is a qualitative method. The subjects used in this study were determined by purposive sampling method. The sample of this study was students of class VIII.5 at MTsN 3 Fifty Kota as many as 3 students, namely those with high ability (NT), medium (RA) and low (RN) of 34 students and 1 math teacher (Buk ITA) ). Data were obtained through student tests with 3 indicators, namely (1) Students were able to express everyday events in language and mathematical symbols in the material on relations and functions. (2) Students were able to describe ideas, situations or pictures in the material on relations and functions. (3) Students are able to connect real objects, images into mathematical ideas on relations and functions. Based on the results of the test data, students' mathematical communication abilities were still relatively low, namely 47% of all class VIII.5 members, students who were classified as moderate, namely 32% of all class VIII.5 members and students who were high, namely 21% of all class VIII members. 5. Accompanied by the results of an interview with one of the class VIII mathematics teachers who said that the level of students' abilities varied according to their efforts.